Understanding Group Maintainership Model in the Linux Kernel Development - Pinheiro, Eduardo; Meirelles, Paulo (Anais do Workshop de Visualização, Evolução e Manutenção de Software (VEM), 2024)
Software development has evolved over decades, transitioning from traditional models such as the waterfall approach and the unified process to more flexible methodologies like agile methods and collaborative development strategies of Free/Libre/Open Source Software (FLOSS) projects. Alongside this trend, the global distribution of software development work has increased. This phenomenon is particularly evident in the development of FLOSS projects, where contributors from various regions worldwide collaborate asynchronously on projects. In this context, the organization of interactions among developers can significantly influence a project success or failure. An example is the Linux kernel community, which has been actively discussing the models and workload of project maintainers – a topic that has received limited attention in scientific literature. This study investigated the new maintenance methods used in the Linux kernel project. With over 30 years of development, the Linux kernel has become a benchmark for FLOSS development. We discuss how the maintainers’ workload is addressed in academic literature and by practitioners in the Linux kernel community. To achieve this, we conducted a multivocal literature review to examine the evolution of maintenance models over the years.